Applying the Cisco Systems™ RLO Model to a Live Automated Training Build for Nationally Dispersed Learners: Takeaways and Lessons Learned - Hai-Jew, Shalin (My University, 2010)
Instructional design theory and practice interact powerfully in live projects. This article describes one use of the Cisco Systems, Inc.’s Reusable Learning Object (RLO) approach (with their legal permission) to the building of automated RLOs for a national project. Through the definition of information as concept, fact, procedure, process, and principle to a live curricular build, a six-module automated training was created in 2006 for deployment beginning in 2007. This project involves 12,000 geographically dispersed learners (of varying educational and cultural backgrounds) with a complex and regionally sensitive curriculum, with contents collected from national SMEs and deployed over an ontologybased database. The training involves evolving biological science materials and requires complex, real-time decisionmaking. This article examines the applied principles of instructional design (cognition, learner profiling, Clark and Mayer’s multimedia development and cognition findings, learner developmental phasing, and other theories) in a live project. It explores how the six modules were planned, created, alpha- and beta-tested and deployed. Vocabulary flashcards, multiple-choice pre- and post-test assessments (for certification), and the beginnings of a decision-making simulation were created. Decision trees were used for the simulation and the planning for a full experience “wrap” for the decision-makers in the simulation. This paper addresses the use of metadata and “invisible” metadata for inhouse password-protected use. Instructor notes added value for the occasions when instructors might choose to deploy the learning live F2F(face-to-face) or via online eLearning using these same digital materials, or when trainers might wish to use online spaces to bring geographically dispersed communities together. Challenges. Real-world strategies for collecting, gaining copyright release, and labeling digital artifacts affected the instructional design. The push for the lowest common denominator among users restricted some curriculum design options. The “affordances” of a database and the collaborative teamwork of dispersed grant principal investigators (PIs) led to yet further limitations. Important multimedia, pedagogical agent strategies, and other elements were harder to create in a cautious environment. This will explore how difficult it may be to create regionalization and customization builds. This will advocate the importance of the malleability and pliability of RLOs for more effective eLearning and reusability.
Keywords: Cisco Systems, Inc.; Reusable Learning Objects (RLOs); Automated eLearning; Instructional design